Effects of Feeding Strategies on Growth Performance of F1 Gulf Coast Striped Bass Strains in Recirculating Aquaculture Systems. (12th July 2022) - Kenter, Linas W.; Skillings, Casey M.; Berlinsky, David L.
Abstract: As feed is a major cost in finfish aquaculture, considerable economic advantages can be gained by optimizing feeding efficiency. In the present study, the effects of reducing feeding frequency were evaluated in Gulf of Mexico strain Striped Bass Morone saxatilis raised in recirculating systems. Juvenile Striped Bass ( 170 g) were raised for 84 d at 21°C and fed three or five times weekly at 3% of body weight (% BW) or three, five, and seven times weekly at 2% BW. In another experiment, subadult fish ( 720 g) were raised at 15°C for 84 d and were fed three or five times weekly at 2% BW. In all experiments, feeding frequency did not affect growth rates or efficiency and fish that were fed less frequently consumed more feed per feeding but typically had reduced feed consumption over the length of the experiment. These results indicate that labor and feed costs may be reduced by limiting the feeding frequency of Striped Bass in recirculating systems .